(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Hypospadias is a developmental anomaly characterized by a urethral meatus that opens onto the ventral surface of the penis, proximal to the end of glans. Fistulas are the most common complication following hypospadias repairs. This study was carried out to see that application of vascularized Tunica Vaginalis Blanket Wrap (TVBW) in urethroplasty reduces fistula rate in hypospadias repair. Objectives: To study the efficacy of Tunica vaginalis blanket wrap to prevent urethrocutaneous (UC) fistula in urethroplasty for hypospadias repair. Methods: Study Design : Prospective comparative study Place of Study :Department of Paediatric surgery, Dhaka Shishu Hospital (DSH), Dhaka. Period of Study :April, 2003 to October, 2004 for a total period of 19 months. The study of population : Twenty (20) admitted patients of hypospadias were selected. Patients were grouped into group A and group B on the basis of lottery method. Group A included 10 cases, who were subjected to repair of hypospadias with the application TVBW. Group B included 10 cases, who were subjected to repair of hypospadias without TVBW. Statistical Analysis : Chi-square test (X2 test) were applied. p value <0.01 was taken as significant. Ethical aspect : Research protocol was accepted by DSH. Written consent were taken from parents. Result: Occurrence of post operated UC fistula found significantly higher in non TVBW. Discussion: In our patients for group A (study group), TVBW was used in urethroplasty while urethroplasty for group B (control group) was carried out without TVBW. UC fistula was present in 1 patient (10%) in group A post operatively and in 5 patients (50%) in group B postoperatively and subsequently 2 more patients developed fistula during follow up period. In control group 7 patient (70%) developed UC fistula out of 10 patients (n=10) despite of using periurethral flap of tissue as second layer over the neourethra. In our study, the rate of development of UC fistula is much less (only 10%) in study group. So the result is significant as evidenced by p value which is less than <0.01.This study demonstrates that use of tunica vaginalis as a blanket wrap as second layer over the neourethra reduces the rate of development of UC fistula. Conclusion: TVBW is recommended for urethroplasty to decrease the postoperative UC fistula. J. Paediatr. Surg. Bangladesh 3(1): 30-36, 2012 (January)